PPX and Concurrent Radiation for Newly Diagnosed Glioblastoma Without MGMT Methylation: A Randomized Phase II Study. (February 2018) - Elinzano, Heinrich; Glantz, Michael; Mrugala, Maciej; Kesari, Santosh; Piccioni, David E.; Kim, Lyndon; Pan, Edward; Yunus, Shakeeb; Coyle, Thomas; Timothy, Kinsella; Evans, Devon; Mantripragada, Kalyan; et al.
Abstract : Purpose: Efficacy signals but substantial myelosuppression were demonstrated in a single arm phase II study of paclitaxel poliglumex (PPX) in combination with temozolomide (TMZ) and radiation therapy (RT) for first-line treatment of glioblastoma. The objective of this randomized phase II trial was to assess the efficacy and safety of single-agent PPX with RT (PPX/RT) versus TMZ with RT (TMZ/RT) for glioblastoma without O 6 -methylguanine-DNA methyltransferase (MGMT) methylation. Materials and Methods: Patients with glioblastoma with unmethylated MGMT without prior chemotherapy or RT were eligible. Patients were randomly assigned 2:1 to PPX, 50 mg/m 2 /wk for 6 weeks, or standard TMZ, with concurrent 60.0 Gy RT. One month after completion of chemoradiation all patients received standard maintenance TMZ. The primary endpoint was progression-free survival (PFS). Results: Of the 164 patients enrolled, 86 were MGMT unmethylated. Of these, 63 patients were randomized (42 to PPX/RT and 21 to TMZ/RT). Fifty-nine patients could be analyzed. The median PFS was 9 months in the PPX/RT group and 9.5 months in the TMZ/RT group (hazard ratio in the PPX/RT group, 1.10; 95% confidence interval, 0.79-2.08; P =0.75). Median overall survival was 16 versus 14.8 months for PPX/RT and TMZ/RT groups, respectively (hazard ratio, 1.44; 95% confidence interval, 0.75-2.77; P =0.27). In the PPX and TMZ groups 44% versus 22% of patients, respectively, experienced one or more grade 3 or higher toxicities during chemoradiation. Conclusions: PPX/RT did not improve PFS or overall survival. This study provides an effective trial design for screening RT sensitizers in glioblastoma.